Can Soybean Seeding Rate Be Used as an Integrated Component of Herbicide Resistance Management?. Issue 4 (December 2014) - DeWerff, Ryan P.; Conley, Shawn P.; Colquhoun, Jed B.; Davis, Vince M.
Abstract : Increased soybean seed cost has generated recent interest in reducing seeding rates to improve economic returns. However, low seeding rates result in reduced established plant stands with slower canopy development, and canopy development is an important element of integrated weed management (IWM). Field studies were conducted in 2012 and 2013 in Wisconsin to determine the trade-off between reduced seeding rates and PRE residual herbicide use for POST herbicide exposure. Soybean was planted in mid May in 38-cm-wide rows at five seeding rates ranging from 148, 200 to 469, 300 seeds ha −1 . A PRE application of metolachlor plus fomesafen was made to half of the plots. One of two POST herbicide programs were sprayed at the V4 soybean growth stage to determine whether blending herbicide-resistant (HR) and non-HR soybean cultivars could be a practical alternative to reduce soybean seed expenses while maintaining the potential benefit of weed suppression before the POST herbicide application. An increase in seeding rate did not reduce the density or size of weeds exposed to the POST herbicide, and furthermore, end-of-season weed density and biomass were not influenced. In contrast, the use of a PRE herbicide reduced total weed density and biomass before POST application by 93 and 95%, respectively, in both years. In 2012, the season was dry early and harvest stands of 161, 100 and 264, 100 plants ha −1 produced 95% of the maximum yield for the PRE and no-PRE treatments, respectively. The difference was not repeated in 2013 with adequate early season rainfall. In conclusion, PRE herbicide use produced maximum yield with fewer plants per hectare by limiting early season weed competition and reduced weeds exposed to POST herbicide application thus contributing to HR management (HRM). In contrast, higher plant densities generated within the seeding rate range of this study did little to improve IWM or HRM.